India-tree variations of strength properties in plantation grown teak (Tectona grandis L.f.) and techniques for their systematic sampling - Sanwo, S (Oxford Forestry Institute, University of Oxford, 1986)
This investigation involved an assessment of the intra-tree variation of some strength properties in teak (Tectona grandis L. f) grown in Nigeria: nominal specific gravity, modulus of rupture (MOR) , modulus of elasticity (MOE), total work done (TWO) and maximum compressive strength parallel-to-grain (MCS). Nine trees were examined from three canopy classes: two dominants, five co-dominants and two sub-dominants. Within each tree, systematic sampling was carried out (a modification of Richardson's (1961) methods). Twenty samples were removed from each tree in positions common to all the trees. Non-standard samples were tested, following the procedure of Wood (1970). Results were analysed by graphical analysis by the method used by Duff and Nolan (1953). The results show that within each tree, the pattern of variation of these wood properties is systematic. This study highlights the techniques of systematic sampling in tropical plantation species, the use of non-standard, small, clear specimens in strength evaluation, and the justification for applying these techniques to fast grown tropical hardwoods. In the Duff and Nolan oblique sequence Specific Gravity, Modulus of Elasticity, Modulus of Rupture, Total Work Done, and Maximum Compressive Strength increased from tree apex to the base. In the horizontal sequence SG, MOR and MCS increased from the pith outwards at different distances from the pith for different properties and then decreased slightly. In the vertical sequence SG, MOR and TWD increased with year of wood formation.